Application of ICT in promoting environmental education among students: The case of marine biodiversity awareness - Selvarajan, Jaya Sankari; Mohd Zahari, Fadhilah (Universiti Utara Malaysia, 2020)
This study aims to identify the application of ICT in promoting environmental education among students concerning marine biodiversity awareness. Sea pollution is getting increasingly high. The awareness of marine biodiversity among youth is not encouraging. Hence, environmental education plays a major role to create awareness about marine biodiversity among students, and ICT could help to promote environmental awareness more effectively and efficiently. Objectives of this paper are two-fold, to identify the extent of student's awareness towards marine biodiversity, and to identify the effectiveness of ICT in promoting environmental education among students. This study uses a quantitative approach through two sets of questionnaires distributed to the 78 respondents along with a video presentation. The results show that the student's score of the quiz is improved after a video presentation shows.